Consumer awareness and the use of payment media: evidence from young Finnish consumers - Ari Hyytinen; Tuomas Takalo (Bank of Finland, 2008)
In the market for payment media, some consumers use only one medium when paying for their point-of-sale transactions, while others use many. This pattern reflects the diffusion of new payment media, because a payment method innovation is typically first used simultaneously with the established methods. We study the use of multiple payment media by employing data on young Finnish consumers. We find that the use of multiple payment media is directly related to consumer awareness and that not controlling for the endogeneity of awareness can bias its effect downwards. These results suggest that increasing consumer awareness may have been underlying the rise of debit card use around the world. It could also speed up the adoption of new means of payment, such electronic money and mobile payments. To the extent that antitrust concerns in the market for payment media stem from the lack of information, improving consumer awareness could be a remedy.
URN:NBN:fi:bof-20140807189
Keywords: G20; E59; 330; payment media; consumer awareness; adoption of financial technology